Antimicrobial and anti-quorum sensing activties of javanese turmeric (Curcuma xanthorrhiza Roxb.) ethanolic extract against Pseudomonas aeruginosa - Othman, Ahmad Fiqri Mustaqim (2018)
Bacteria such as Pseudomonas aeruginosa uses quorum sensing (QS) mechanism to regulate the production of virulence factors, swarming motility and biofilm formation. As the synthetic quorum quenching compounds such as halogenated furanones reported to be toxic for human, using medicinal plant as an alternative as an anti-quorum sensing agent have been gaining attention. The objective of this study was to evaluate the antimicrobial and the antiquorum sensing activities of the C. xanthorrhiza Roxb. extract on the P. aeruginosa ATCC35554. The rhizome of the C. xanthorriza Roxb. was extracted using ethanol as the solvent. The crude extract were tested for antibacterial activity against P. aeruginosa in terms of well diffusion, minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) using the Clinical and Laboratory Standard Institute (CLSI) methods. Additional analysis on the antimicrobial activity of the extract was done on the bacterial growth using the Log10 colony forming unit assay. The quenching of QS mediated swarming was done by measuring the mean diameter of the swarming colonies treated with the C. xanthorrhiza Roxb. extract. The pyocyanin inhibition was evaluated colorimetrically by extraction with chloroform and 0.2 M hydrochloric acid (HCl). As for the alkaline protease and the LasB protease, the supernatant of the culture treated with the extract were exposed to the skim milk agar and the casein buffered broth. Biofilm formation prevention was done using the 2, 3-bis (2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenyl-amino) carbonyl]-2H-tetrazolium- hydroxide (XTT) reduction assay on a pre-sterilized 96-wells microtiter plate. The results showed that the extract can inhibit and kill the growth of the P. aeruginosa with MIC and MBC values of 200 and 700 mg/mL, respectively. This indicates that the inhibition and killing of this bacterium need a relatively high concentration. Up to 200 mg/mL of the extract was used in the antibacterial assay as in the quorum quenching assays, 50 mg/mL of the extract did not exhibited significant inhibition. Interestingly, the extract at 200 mg/mL showed 72.12% reduction of swarming motility, 84% inhibition of the pyocyanin production, 50.14% and 40% decrement of alkaline protease and LasB protease secretion, respectively and 78.35% decrease in the biofilm formation. Since production of the QS virulence factors, swarming and biofilm has been known to be regulated by the multiple QS circuits, the quorum quenching activities by the ethanolic extract of the C. xanthorriza Roxb. suggest that it can interfere on these systems. In conclusion, the C. xanthorriza Roxb. extract shows a high potential for an alternative natural quorum quenching agent.